2015
DOI: 10.1194/jlr.m056481
|View full text |Cite
|
Sign up to set email alerts
|

Defective triglyceride biosynthesis in CETP-deficient SW872 cells

Abstract: with adipose tissue CETP mRNA levels in both man and hamster ( 6,7 ), showing the importance of this tissue in both lipid storage and the modulation of intravascular lipid metabolism.While most CETP is secreted by cells, a portion is retained ( 8-10 ). Much of the intracellular CETP pool is associated with the endoplasmic reticulum (ER), with increased concentrations near lipid droplets ( 8,11 ). Both cytoplasmic and lipid-droplet pools of CETP have been observed as well ( 11 ). Although the mechanism for CETP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…5A). The CETP-specific antibody TP2 reduced transfer by E9-deleted CETP to baseline levels, similar to that previously reported for FL CETP (24). In this experiment, similar levels of FL and E9-deleted CETP mass, based on Western blot analysis, were used for the assay.…”
Section: E9-deleted Cetp Transfer Activitysupporting
confidence: 79%
See 2 more Smart Citations
“…5A). The CETP-specific antibody TP2 reduced transfer by E9-deleted CETP to baseline levels, similar to that previously reported for FL CETP (24). In this experiment, similar levels of FL and E9-deleted CETP mass, based on Western blot analysis, were used for the assay.…”
Section: E9-deleted Cetp Transfer Activitysupporting
confidence: 79%
“…We have previously shown that the extent of 3 H-oleate incorporation under these conditions mirrors the mass of these lipids present in SW872 cells (14,15). In our earlier studies, we demonstrated that reducing both FL and E9-deleted CETP expression caused newly synthesized TG to accumulate in an ER-rich fraction instead of lipid droplets, the natural TG storage site (15,24). A similar study was performed in cells overexpressing E9-deleted CETP to determine whether their increased TG content could arise from increased TG synthesis and/or altered incorporation of this TG into lipid storage droplets.…”
Section: Effect Of E9-deleted Cetp On Lipid Metabolism In Sw872 Cellsmentioning
confidence: 77%
See 1 more Smart Citation
“…This remains to be tested experimentally. Alternatively, several studies have shown that human CETP also functions inside cells to control the accumulation of CE and TG in lipid droplets ( 11 , 42 , 43 ). The expression of human CETP may modify this process in the livers of fat-fed hamsters causing cholesterol to accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented here could support the first hypothesis if intracellular CETP alters lipid delivery from LDLR‐derived endosomes to TG metabolic and nuclear receptor targets. In vitro work supports a role for intracellular CETP in regulating TG metabolism and LDL uptake in adipocytes and liposarcoma cells (Greene et al, 2015; Izem et al, 2015; Izem & Morton, 2007). The second hypothesis, however, may more easily explain the broad functional impacts of LDLR deletion on CETP function in TG metabolism.…”
Section: Discussionmentioning
confidence: 66%